PENGARUH MEDIA PEMBELAJARAN FLIPBOOK UNTUK MENGEMBANGKAN KEMAMPUAN LITERASI BACA TULIS MATERI SUMBER DAYA ALAM KELAS IV SEKOLAH DASAR - Munawaroh; Immamudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to explore the effect of using flipbook media in learning on improving the literacy skills of fourth-grade elementary school students on natural resources material. The study was conducted at Banjar Agung 4 Elementary School using a quantitative approach and a one-group pretest-posttest pre-experimental design. The research subjects were 29 students. Data collection techniques included pretest, posttest, questionnaire, observation, and documentation. The results of the analysis showed that there was an increase in the average value from the pretest to the posttest stage. The normality test indicated that the data were normally distributed. The t-test showed tcount > ttable (22,365 > 2,121) with a significance value of 0.000 < 0.05, so the null hypothesis H0 was rejected. The N-gain test showed an average of 0.77 which was in the moderate category. These results indicate that the use of flipbook media had a significant impact on improving students' literacy skills.